2021
DOI: 10.1111/ddi.13406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different scenarios of temperature rise and biological control agents on interactions between two noxious invasive plants

Abstract: Aim: An increasing number of exotic plants and their biological control agents are being introduced into new regions. Therefore, it is necessary to study their interactions and to manage the future directions of plant invasions under different scenarios of temperature rise. Location: China. Method: We investigated the distribution patterns of the two most prevalent invasive aquatic plants in the world, Alternanthera philoxeroides and Eichhornia crassipes, at a large scale and studied the interactions of both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…A study found that native plants benefit from warming more than invasive plants, and this asymmetry, in effect, may decrease the relative abundance of invasive plants [ 29 ]. Another study found that regardless of warming conditions, invasive and native plants were similar in their responses in terms of total biomass, leaf and root areas, biomass allocation, temperature sensitivity, and phenotypic responses [ 30 ]. However, a study found the opposite result, where warming was generally more beneficial to invasive plants than native plants [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study found that native plants benefit from warming more than invasive plants, and this asymmetry, in effect, may decrease the relative abundance of invasive plants [ 29 ]. Another study found that regardless of warming conditions, invasive and native plants were similar in their responses in terms of total biomass, leaf and root areas, biomass allocation, temperature sensitivity, and phenotypic responses [ 30 ]. However, a study found the opposite result, where warming was generally more beneficial to invasive plants than native plants [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, specialist herbivores may lower the population expansion speed of invaders but cannot eliminate or reduce the developed population. What's more, in multi-invader communities, it is rare that specialist herbivores of each invasive plant appear and all plants are effectively controlled (Zhang et al 2021b). Even if enemies can successfully control one invasive plant, the co-occurring invasive plants can still dominate the communities (Center et al 2005, Hill et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas climate warming can facilitate the establishment and dispersal of exotic aquatic plants by altering streamflow and thermal regimes, reducing ice cover in waterbodies, and increasing water development activities (Rahel and Olden 2008). In addition, climate change has the potential to influence plant invasions by influencing native communities and co-occurring exotic plants (Li et al 2017, Zhang et al 2021b. Given the complexity of the effects of climate change on biological invasion, the study on predicting biological invasion under climate change should involve numerous invasive species, multiple measures of invaders, and the interactions between native and invasive plants, as well as among invaders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations